Proses Penciptaan Teater Dalam Monolog Naskah “Berusaha Melawan Lupa” Karya : Acep Zam Zam Noor Pada Festival Lanjong ART Festival (LAF) Kutai Kertanegara Kalimantan Timur - Giri Mustika Roekmana (Pendidikan Seni Drama Tari dan Musik, Universitas Sultan Ageng Tirtayasa, 2019)
Abstract : Monologue art is a drama performing art that is played by one actor and can play several characters in the story. How to play this monologue art is quite difficult because an actor must work extra practice and look for lots of references. The ability of a monologue player must be multi-talented, he must master good vocal techniques, he must master the techniques of a trained body, he must have trained emotional intelligence so that the character of the characters in the monologue script can be maximally realized. In this study the author wants to convey information related to how to play a monologue and present it. The concept of presenting monologues is not much different from the concept of presenting drama in general, only the difference is being played by one actor. On this occasion the author took the moment of the process of creating a monologue at the Lanjong Art Festival held by the East Kalimantan Kutai Kartanegara Lanjong Foundation. The monologue manuscript was titled